Evaluating the use of loop-mediated isothermal amplification (LAMP) method for detection of Mycobacterium tuberculosis in Indonesian clinical isolates (Faculty of Medicine Universitas Indonesia, 2012)
Background: Loop-mediated isothermal amplification (LAMP) is a method already claimed as a simple technique to amplify DNA/ RNA using four to six primers as